Conceptual Study Of Enzymatic Synthesis Of Propyl Caffeate In Packed Bed Reactor At Steady-State And Isothermal Conditions - Rajendran, Ajayan (Universiti Sains Malaysia, 2021)
The enzymatic propyl caffeate synthesis in packed bed reactor (PBR) at steady-state and isothermal conditions is presented in this thesis. The simulation carried out to study the effects of temperature, substrate/alcohol molar ratio, and substrate concentration on conversion. The mathematical model is developed in Polymath® software to simulate the results to compare with published experimental data. The highest conversion achieved at 60°C with 99.5% in the experimental data while the proposed simulated data gives 91.1% at 60°C with the error percentage of 8.44% which is considered acceptable error percentage since less than 10%. Based on this simulation results, both conversion and rate of reaction is decreases at reaction temperature above 80°C which shows the enzyme are start to deactivate at this temperature. This study shows the highest conversion is achieved in both simulation and experimental results at reaction temperature of 70°C and 60°C respectively. Moreover, both simulated and experimental results indicates that the perfect molar ratio of methyl caffeate to 1-propanol is with range of 1:10 and 1:40 which give higher conversion and producing high yield. In addition, the studies found that low concentration of methyl caffeate of 0.005 mol/L provide the highest conversion and enhances the enzymatic reaction.